(3QSGdI aj Cf GdReGf GdeJfGgi MQcI ZjQ eJfGgjIs - (3nhrjnLf Hf QSJe Gdochgj (B( (3Gdbhgj (B) (3, CHh Sgd,J (B390 (3g` s
(3ChdgG (B:s
(3faQV fUa OGFQI C O H Ydi bWQ C L heQcRg fbWI O hfJhge Ydjg TNUkG bGFekG hgh O g` s
(3BNQgG (B:s
(3hcPdc ai GdfUa GdBNQ jHjf Cf MQcI QCS GdTNU djS dg efJgi hPdc eG CQOfG Cf fHjf JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYTQhfs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B175s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs